Resilience of Sweet Chestnut and Truffle Holm-Oak Rural Forests in Languedoc-Roussillon, France: Roles of Social-Ecological Legacies, Domestication, and Innovations - Aumeeruddy-Thomas, Yildiz; Therville, Clara; Lemarchand, Cedric; Lauriac, Alban; Richard, Franck (Ecology and Society)
The Cvennes sweet chestnut (Castanea sativa Mill.) forest-orchards and the holm-oak (Quercus ilex L.) black truffle (Tuber melanosporum Vittad.) associations of the garrigue in Languedoc-Roussillon have suffered a century of decline because of great reductions of rural populations and lack of understanding of the ecological and social dimensions of these rural forests by sectorial public agencies. Levels of tree and forest domestication alternated during historical periods in parallel with statuses of disorganization and reorganization of local social groups. Social-ecological legacies intrinsically linked to trees, forests, and landscape domestication, as well as knowledge, social, and technical practices have been mobilized and provided a basis for knowledge innovations, new domestications, uses, and new institutional networks related to changes in social set-ups. Collective actions emerging from local needs to revive territories in a modern context, cross-scale and reciprocal exchanges of rural and scientific knowledge, as well as institutional changes are interrelated variables that have enabled innovations and have increased resilience of these rural forests. This paper opens new avenues for future research on the interplay between the effects of social-ecological legacies and innovations on the resilience of social-ecological systems.
Keywords: Cévennes; chestnut; domestication; Garrigue; holm-oak black truffle association; innovations; resilience; rural forests; social-ecological legacies

Starch isolation from chestnut and acorn flours through alkaline and enzymatic methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Food and Bioproducts Processing, 2012)
Two different procedures were used to isolate chestnut (Castanea sativa Mill.) and acorn (Quercus suber) starch. Starch was extracted from the ﬂour of these dried fruits by: (i) low shear at alkaline pH and successively using three sieves (A3S) at different centrifugation conditions (velocity and time) and (ii) enzymatic treatment at low shear (ENZ) at a different amount/digestion time of protease. In both cases a Central Composite Rotatable Design (CCRD) was used as an experimental design. Results were treated through the Response Surface Methodology (RSM). Based on maximum yield values and the degree of purity, the best modiﬁed conditions encountered were applied in a new trial and mass balance was established for both isolation procedures. The best centrifugation conditions encountered for the A3S isolation method were 800 × g during 15min, and for the ENZ method 900 units of protease despite the incubation time, for the same centrifugation terms. The yields reached with these experimental conditions for the A3S and ENZ methods were 83.9% and 79.9% for chestnut and 88.5% and 86.9% for acorn, respectively. Isolated starches shown to be higher in purity, presented values of 98.3% and 96.3% for chestnut and 98.1% and 97.6% for acorn, respectively for the A3S and ENZ methods
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: acorn; chestnut; composition; isolation method; starch; yield

Chestnut and acorn starch properties affected by isolation methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Starch - Stärke, 2010)
Starches from chestnut (Castanea sativa Mill.) and acorns (Quercus suber Lam. and Q. rotundifolia Lam.) were isolated from dried fruits using four different methods. These involved a physicochemical and/or an enzymatic treatment followed by centrifugation and sieving: (i) low shear at alkaline pH – LSA, (ii) high shear in water – HSW, (iii) enzymatic treatment at low shear – LSE, (iv) LSA and using successively three sieves – LSA3S. Raw yield, purity, colour parameters, morphology, protein, fat, ash, reducing sugars and amylose contents, damaged starch content and viscoamylographic proﬁles were studied in isolated starches, presenting different properties through different methods. In general, chestnut starch seems to be poorly resistant to extraction methodologies as shown by the damaged starch content and viscoamylographic properties encountered during this study. Moreover, acorn starches exhibited cross-linked amylographic patterns. For all the tested raw materials, the LSA3S isolation method always higher yield and purity of starches. Gelatinization temperature and peak consistency were also higher than those shown by starches produced by the other methods, a less damaged structure was also evident. In conclusion, it seems that this method is the most suitable to produce starch for food ingredient usage.
Keywords: acorn; chestnut; morphology; physicochemical properties; starch isolation methods